Solvent-free production of protein-enriched fractions from navy bean flour using a triboelectrification-based approach. (April 2016) - Tabtabaei, Solmaz; Jafari, Mousa; Rajabzadeh, Amin Reza; Legge, Raymond L.
Abstract: Conventional plant protein production methods involve the use of solvents, concentrated acids and alkali that can result in protein denaturation and loss of solubility, thereby reducing the quality and functionality of protein ingredients. A novel solvent-free tribo-electrostatic separation approach was developed for the production of high quality plant protein powders using navy bean flour as a model system. The process consisted of a fluidized bed flour reservoir, tribo-charging unit, and a separating device. Using this approach the protein content of the original navy bean flour was increased from 25.4% to 47.0% in the final protein-enriched fraction collected from the bottom section of the plate in the separator. A wide variety of tribo-charging tubes with different sizes, shapes, and materials were tested to evaluate their efficiency. Protein recovery by this approach was higher than other solvent-free separation approaches and could be improved by further optimization of the flow rate and design configuration of the separator. Highlights: A solvent-free electrostatic-based plant protein separation approach was developed. Separator consisted of a fluidized bed, tribocharger and a separating chamber. Polytetrafluoroethylene (PTFE) showed the highest triboelectrification efficiency. Protein and carbohydrate were charged to different levels using PTFE tribocharger. Protein and carbohydrate-enriched fractions were produced from Navy bean flour.